COMPARISON OF CLINICAL CHEMISTRY ANALYSIS RESULTS PREPARE FROM INNOMED BLOOD COLLECTION TYPES LITHIUM HEPARIN BLOOD COLLECTION TUBES AND SODIUM FLUORIDE BLOOD COLLECTION TUBES - Wongsom, Mayuree Rattanaphan (Journal of MCU Nakhondhat, 2023)
The objective of the research is 1) to study the efficiency of biochemical analysis from the use of Innomed tube products, 2) to compare the results of biochemical analysis between the use of Innomed tube products and lithium heparin blood collection tubes, and 3) to compare the blood glucose levels of plasma prepared from Innomed blood collection tubes and sodium fluoride blood collection tubes after blood collection within 0, 4, and 8 hours. The sample used in the study was blood that was used to measure glucose levels and various biochemicals in Koh Samui Hospital between 1 Nov. 2022 to 31 Mar. 2023 to measure glucose levels and various biochemicals by automatic analyzer covering 20 biochemical measurements. Data were analyzed using mean, standard deviation analysis and compared the results using Paired t-test. The results showed that 1) the efficiency of the analysis of 20 biochemicals from the use of Innomed tube showed the analytical values within the specified range. 2) Results of biochemical analysis during use of Innomed blood collection tube products and lithium heparin blood collection tubes, it was found that there was no difference at the statistical significance level of 0.05. 3) Results of the analysis of differences in blood glucose levels of plasma prepared from Innomed blood collection tubes and sodium fluoride blood collection tubes after blood collection within 0, 4, and 8 hours were found to be no different at the statistical significance level of 0.05. Therefore, the researcher suggests that Innomed tube products be used in Koh Samui Hospital and disseminate to other hospitals to bring Innomed tubes to use with patients who come to receive services efficiently.